Optical fiber communications : principles and applications - Singal, Tarsem Lal (Delhi, India : Cambridge University Press is part of the University of Cambridge, 2016)
'Discusses several dispersion-management schemes that restore amplified signal to its original state'--
Includes bibliographical references (page 441-443) and index.
Keywords: Optical fiber communication